Sigmund Neumann - der totale Demokrat Eine intellektuelle Biographie - Graf, Marie-Sophie (Mohr Siebeck, 2021)
The historian and political scientist Sigmund Neumann (1904-1962) was German, Jewish, and a democrat. Socialized in the German Empire and the Weimar Republic, he emigrated to escape Nazi persecution. Today, his ideas on democracy and totalitarianism have almost been forgotten. In her study of Sigmund Neumanns life and work Marie-Sophie Graf argues that they remain relevant even today.
PublicationDate: 20211215
Keywords: Ideengeschichte des Konservatismus -- fiscal rule -- Parteienforschung -- Totalitarismustheorie -- Anfänge der deutschen Politikwissenschaft -- unverletzlich -- Sozial-/Kulturwissenschaften -- 19.-21. Jahrhundert -- Jüdische Geschichte -- Wissenschaftsgeschichte